THE AUTHORITY OF ADMINISTRATIVE COURT IN SETTLING THE DISPUTES OVER ELECTION PROCESS IN INDONESIA - Oce Madril (Faculty of Law, Universitas Sebelas Maret, 2019)
Indonesia is a country that provides constitutional guarantees over the principle of popular sovereignty. A manifestation of the principle of popular sovereignty is through the holding of a General Election. To safeguard the implementation of fair and democratic elections, laws and regulations concerning elections are made by the government. One of the principles of fair and democratic elections is the availability of legal mechanisms to resolve election disputes. The Indonesian Election Law already has these rules. One mechanism for resolving election disputes is through state administrative courts. This research focuses on discussing the development of the authority of the State Administrative Court (PTUN) in resolving disputes over the Election process. The PTUN has long been established in Indonesia, but the authority of the PTUN in resolving election disputes is a new authority expressly granted by the post-reform election law. This study also discussing two PTUN decisions. The decisions show how electoral law is applied in the practice, which is sometimes not always the same as what is expected by legislators.